Transformation Model for Online Trials at the Bekasi District Court - Widodo, Aan (Jurnal Komunikasi, 2024)
During the pandemic, law enforcement was carried out online in many courts around the world, including the Indonesian courts. The implementation of this online trial involves law enforcement as the party conducting the online trial. There are many challenges faced related to how online trials are managed, changing law enforcement procedures, including how technology is used in trials by law enforcers to support trials, however online trials are still implemented through the support of communication processes. This research aims to describe the transformation process carried out by law enforcers during the implementation of online trial communication. The concepts used are trial transformation, communication and diffusion of innovation. This research was conducted qualitatively using a phenomenological approach, the researcher conducted interviews with 7 informants consisting of 2 judges, 3 prosecutors and 2 legal advisors, the researcher also conducted analysis on archived online trial recording documents. The results of this research show that online trials are carried out as an implication of physical and social restriction policies, as well as a form of developing online-based trial services. The transformation process carried out by law enforcers during the implementation of online trial communication is carried out using two transformation models, namely the personal transformation model and the institutional transformation model. Success in implementing online trials as a form of transformation is influenced by the quality of infrastructure, law enforcement literacy, communication established between parties, namely communication between institutions, including the court, prosecutor's office, police, and law offices.